Development of dish-stirling concentrating solar thermal-electric energy conversion system - Gan, Leong Ming (2012)
Sunlight is the world's largest renewable energy source. Using the existing technologies,this energy can provide the needs of all the people on Earth.By increasing the solar-to-electric energy conversion efficiency while maintaining the cost and lifespan of a machine,conventional photovoltaic technology is being progressively challenged by concentrated solar thermal engine technology especially in large scale power plant.For local research,the limitation of technological development between technical potential and practical utilisation of solar energy becomes one of the reasons behind the minimum growth of solar energy field. Owning a local renewable energy conversion system means decrease fossil fuel dependability,secure near to long term power supply chain and hence enhances economic development. In order to develop local expertise with low production cost, full scaled dish-Stirling CST based on DNI solar flux modules were prototyped.The development of the research began with a preliminary assessment on a 2m diameter manual operated ideal paraboloid concentrating dish prototype.Based on the important design parameters and followed by rigorous system design principles,an 8m diameter combined paraboloid-Fresnel concentrating dish with low focus height, low dish height and minimal wind resistance was designed and constructed.Using the hydraulic-electric two-axis solar tracking system,the proposed system was able to move 0-90 0 in Azimuth axis and +I1800 elevation axis for the full day solar tracking with the consideration of yearly solar path variation.For the thermal-to-mechanical energy conversion,a compact and superior combination of square configuration, four cylinders rhombic drive beta drive mechanism Stirling engine system was integrated with the concentrating dish and tracking mechanism. Throughout the research and development,detailed investigations were conducted to achieve correct operation of the actual prototype.Referring to the 3D model,these studies,including a 3D ray trace analysis on the dish's focal region solar flux concentration pattern, influent of Azimuth angle offset on the thermal receiver performance,air flow simulation on +1- 0 to 28m1s wind load, coefficient of drag comparison and stress distribution due to wind and structural loads.From the computational and operating analysis, the paraboloid-Fresnel dish showed 34.9 to 38.3% of wind load reduction compared with ideal paraboloid design,low CD in between 0.077 to 0.76 depends on wind flow direction and rotating angle.Together with structural mass,stress simulation indicated maximum stress of 320.6JVINIm2 and was validated with six components failure.Meanwhile,practical model showed 51% of structural stress reduction after continuous design improvement.Next,focal region temperature readings were recorded under various circumferences,and maximum concentrated temperature of 357°C had agreed the research hypothesis that specific thermal receiver design can store the solar flux at higher intensity.After several cranking tests, the prototype Stirling engine was unable to start as designed due to scattered solar thermal distribution.Based on Schmidt's analysis, the predicted engine output power was 6.03kW. Considering the total energy consumption for PLC, electric motor,hydraulic system and auxiliary system,the net power output was predicted at 5.759kw.Based on 1000W/m2 solar DNI, the energy conversion efficiency for 8m diameter concentrating dish was predicted at 11 .52%.